Association of Complete Blood Count Parameters with Gestational Diabetes Mellitus - Zehra Vural Yılmaz; Elif Yılmaz; Bilal İçer; Tuncay Küçüközkan (Medical Network, 2017)
Objective: The aim of this study is to evaluate the relationship between hematological changes in early pregnancy using complete blood count parameters and gestational diabetes mellitus. Study Design: One hundred pregnant with gestational diabetes mellitus and one hundred healthy pregnant were included in the study. Blood samples for routine complete blood count parameters in first trimester of pregnancy were analyzed. Results: In the gestational diabetes mellitus group white blood cell, platelet count, neutrophil and lymphocyte count, mean platelet volume, red cell distribution width were significantly higher than control group. However, there was no significant difference between groups with regard to neutrophil to lymphocyte ratio and platelet to lymphocyte ratio levels. In binary logistic regression analysis; first trimester mean platelet volume and red cell distribution width values were found to be independently associated with diagnosis of gestational diabetes mellitus. Conclusion: This study demonstrates that hematological parameters in first trimester of pregnancy are closely associated with gestational diabetes mellitus. The parameters that are routinely and automatically calculated in complete blood count; may be used to predict gestational diabetes mellitus.